WI2020 Zentrale Tracks 2020
DOI: 10.30844/wi_2020_h4-haddad
|View full text |Cite
|
Sign up to set email alerts
|

Business Model Choice Matters: How Business Models Impact Different Performance Measures of Startups

Abstract: Determining the influencing factors of business performance is an important topic in theory and practice. This applies especially to the entrepreneurship context, characterized by extreme uncertainty and high failure rates. Existing research, which is mainly qualitative, has identified business models (BM) as a performance determinant. This paper empirically examines the relationship between BMs and startup performance. The analysis follows an industry-and region-independent approach and is based on a dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
10
0
3
Order By: Relevance
“…Studies showed that business model innovation, in particular, became the success and a valuable capability of a firm (Aspara et al 2010;Lindgardt et al 2009;Chesbrough 2010;Amit and Zott 2012). In terms of the start-up, some business model patterns found to outperform others on different performance measures to the success of start-up (Haddad, et al, 2020). The contractor pattern seems to enhance revenue and cash flow, while add-on patterns influence growth.…”
Section: Business Model Innovationmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies showed that business model innovation, in particular, became the success and a valuable capability of a firm (Aspara et al 2010;Lindgardt et al 2009;Chesbrough 2010;Amit and Zott 2012). In terms of the start-up, some business model patterns found to outperform others on different performance measures to the success of start-up (Haddad, et al, 2020). The contractor pattern seems to enhance revenue and cash flow, while add-on patterns influence growth.…”
Section: Business Model Innovationmentioning
confidence: 97%
“…The business model canvas comprises nine basic building blocks, namely; the customer segment, value proposition, channel distribution, customer relationships, key resources, key activities, key partnerships, revenue streams, and cost structure. According to Haddad et al (2020), there are existed business model patterns that can represent the aspects of the business model innovation. These business model patterns are subscription, advertising, pay per use, freemium, add-on, premium, contractor, long tail, data as a service, cross-selling, e-shop, crowdsourcing, multi-sided platform, ultimate luxury, and customer lock-in.…”
Section: Business Model Innovationmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of business model has attracted increasing attention from practitioners and scholars in micromanagement research (Foss and Saebi, 2017;(Haddad et al, 2020;Wieland et al, 2017;Zott et al, 2011). However, it lacks an established definition and clear theoretical foundation (Wieland et al, 2017).…”
Section: Business Model Innovationmentioning
confidence: 99%